Assessing the influence of pod storage on sugar and free amino acid profiles and the implications on some Maillard reaction related flavor volatiles in Forastero cocoa beans. (September 2018) - Hinneh, Michael; Semanhyia, Evangeline; Van de Walle, Davy; De Winne, Ann; Tzompa-Sosa, Daylan Amelia; Scalone, Gustavo Luis Leonardo; De Meulenaer, Bruno; Messens, Kathy; Van Durme, Jim; Afoakwa, Emmanuel Ohene; De Cooman, Luc; Dewettinck, Koen
Abstract: The practice of pod storage (PS) has been applied in many cocoa producing countries, especially by Ghanaian farmers over the years. However, the study of PS has not received much attention, hence, until now, its potential impact on specific flavor precursor development and implications on the flavor of cocoa beans still remains uncovered. The study was therefore aimed at exploring this possibility through physico-chemical and flavor precursor analyses, carried out on equally fermented and dried pod stored (0, 3 and 7 days) Ghanaian cocoa beans. Flavor analysis was also conducted on equally roasted pod stored cocoa beans. Through visual assessment of the pods, pulp and beans, the compelling impact of PS on fermentation index (FI) and nib acidity could be demonstrated by the various biochemical and physical changes such as respiration, moisture reduction, and cellular degradation, occurring during the process. Whereas the entire reaction of sugar degradation may be deemed complex, a clear relationship between the FI, nib acidity and the glucose content was observed. Also, PS was found to increase with marginal increase in total reducing sugars (glucose and fructose). Although the concentration of free amino acids was directly proportional to the duration of PS, within the framework of this study, a significant difference ( p  < .05) was only observed in the case of extended duration (7 days). Overall, 7 PS seemed to have enhanced the formation of more volatiles. This was followed by 0 PS and finally 3 PS. Suggestively, these findings could provide some indications in explaining the typical flavor profiles of the Ghanaian cocoa beans, considering the fact that 87.8% of Ghanaian farmers adhere to this practice. Meanwhile, for the chocolate industry, the surging demand for cocoa/chocolate products exhibiting unique flavors, could be partly addressed by adopting PS as a tool for varietizing the flavor capacity of "bulk" cocoa through the expression or suppression of specific flavor precursors in the raw material on the farm level, which comes with almost no additional cost. Graphical abstract: Unlabelled Image Highlights: 87.8% of Ghanaian cocoa farmers practiced PS. 97.7% stored their pods between 1 – 7 days, whereas, 2.3% exceeded 7 days. Total reducing sugars increased from 0 to 3 days of PS. However, this was marginal between 3 and 7 days. Extended PS (7 days) resulted in a significant increase in free amino acids. Of the identified volatiles, 7 days pod stored cocoa beans recorded the highest total volatile concentration.